Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Kepuasan Kerja Pegawai Badan Pemeriksa Keuangan Provinsi Sumatera Selatan (BPK) - Wijaya, Muhammad Candra; Roni, Mukron (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The purpose of this research is to determine the effect of leadership and compensation on employee performance at the South Sumatra Representative Financial Supervisory Agency, where the sample size in this research was 151 respondents using questionnaire data collection techniques, with Likert scale measurements. This research is quantitative in nature using validity, reliability, classical assumption tests, multiple liner regression using SPSS 25. Where in this research leadership and compensation have a partial effect on employee performance at the South Sumatra representative Supreme Audit Agency and leadership and compensation have a simultaneous effect on the performance of employees at the Sumatra representative Financial Audit Agency.